Physical fitness profiles of elite freestyle male and female wrestlers - Gierczuk, D.; Cieslinski, I.; Buszta, M.; Sadowski, J. (Theory and Practice of Physical Culture, 2020)
account of their weight classes and performance in tournaments. The study participants were 72 female wrestlers and 66 male wrestlers who had won medals or had placed fifth to eighth at Poland Senior Championships or other major sports events. Subjects` physical fitness profiles were assessed by measuring their explosive strength, strength endurance, suppleness, special endurance and agility. Differences were found between the profiles of male and female wrestlers, and of lightweight and heavyweight wrestlers of the same gender. Female wrestlers had lower scores than men for explosive strength, special endurance, strength endurance and suppleness while being more agile. The analysis of wrestlers` profiles with respect to their body mass showed that both male and female wrestlers in the lightweight classes were more agile and supple than their counterparts in the heavyweight classes, with the lightweight male wrestlers also having higher scores on the strength endurance test. The study demonstrated that the key abilities that both male and female wrestlers need to win medals are strength endurance, special endurance and explosive strength. The performance of lightweight female wrestlers primarily depends on their strength endurance and special endurance. In the case of lightweight male wrestlers, agility is an essential ability.